(untitled) (Research, Society and Development, 2020)
Objective: the research aimed to analyze the performance of nursing in a Psychosocial Care Center in the northeastern semiarid. Method: the research has a descriptive character with a qualitative approach and focus, carried out in a Psychosocial Care Center for Alcohol and Other Drugs 24 hours in the backlands of Pernambuco with nine nursing professionals, five nurses and four nursing technicians. The empirical material was produced through semi-structured interviews and analyzed using the discourse analysis technique. Results: still fragmented view of nursing, with a focus on health problems and focused on uniprofessional care; difficulties in integration with other professionals and failure to recognize their competence in the area of ​​psychosocial care. Final considerations: in general, nursing still presents impediments in inserting itself in the context of psychosocial care, and it is necessary to reorganize the modes of care so that what is proposed in the Brazilian psychiatric reform becomes effective, an innovative posture of professionals who prioritize the person and health promotion.